Perceptions of blended learning among 3D animation lecturers at a higher education institution and its influence on the teaching and learning process - Fong, Leroy Kien Ynn; Poon, Stephen (Penerbit Universiti Kebangsaan Malaysia, 2021)
This paper presents a critical qualitative review and analysis of blended learning (BL) in the creative design education environment from the perspective of animation lecturers through examining their observations, shared experience, technology adoption, and perceptions of BL benefits. The aim of study is to understand how design lecturers adopt their teaching strategy to a blended learning environment, and how their challenges could influence the direction of current pedagogical research in the use of BL to teach design courses. Using interpretative analysis of narrative themes, the paper charts the blended teaching experiences of five 3D animation educators at a Malaysian higher education institution (HEI) through qualitative, interpretive analysis. Findings reveal that among the three factors of technology concerns, personal conviction and disruptions, the greatest challenge to perceptions towards BL environment is clarity of management goals, as well as factors like social communication and technical support to ensure educators can cope successfully in adopting digital learning management platforms such as LMS. Significantly, findings pinpoint the challenge of cohesive management policies and directives to address design academics’ lack of training and experience in adopting blended learning and designing meaningful teacher-learner interactions. In conclusion, recommendations are provided on how to improve design education blended learning pedagogical models, through emphasising the role of social communication, and to ensure clarity of management directives by redefining the potential of utilising blended learning for robust outcomes in design education.